Patient‐reported outcome measures in psoriasis: the good, the bad and the missing!. (1st May 2015) - Kitchen, H.; Cordingley, L.; Young, H.; Griffiths, C.E.M.; Bundy, C.
Summary: As a long‐term condition, psoriasis demands significant personal and professional input for optimal self‐management. Low levels of well‐being and high levels of psychological distress in patients with psoriasis are associated with reduced resources for self‐care. Patient‐reported outcome (PRO) measures can be used to assess physical, social and psychological functioning in order to guide treatment. In this article, we systematically reviewed the development and validation of existing PRO measures. PubMed (Medline), PsycINFO and CINAHL were searched systematically using predefined search terms. The search was limited to articles in the English language relating to human subjects. Articles were selected for full review through explicit inclusion/exclusion criteria. PRO measures were critically reviewed in accordance with the published guidelines and theory on the development and validation of PROs. The search identified 967 abstracts; 71 of these articles met the criteria for full review. In these 71 articles, 45 PRO measures were found: 16 were specific to psoriasis, 21 assessed other dermatological conditions and eight were developed for generic nondermatological health conditions. The review revealed several limitations of the existing measures, including: (i) a composite structure assessing multiple, poorly‐defined concepts; (ii) a lack of evidence for face and content validity; (iii) a failure to include both patient and clinician perspectives and requirements and (iv) a lack of evidence regarding the feasibility and acceptability for patients and physicians. No single PRO measure with adequate evidence of validity, reliability and sensitivity to change captures patient well‐being in psoriasis. A valid, sensitive, specific and acceptable PRO that assesses the full impact of psoriasis on well‐being is needed for the comprehensive clinical management of psoriasis.